KONSEPTUALISASI DASAR PROFESI DALAM MEMBENTUK KARAKTER KERJA GENERASI Z DI TENGAH DINAMIKA BUDAYA KERJA KONTEMPORER - A Azka Ardan Fikrussofa; Siti Aimah (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the relevance of fundamental professional concepts to the development of professionalism among Generation Z as they navigate the dynamics of the contemporary workplace. This research is significant because advancements in digital technology, shifts in work culture, and increasing professional flexibility influence how Generation Z perceives professionalism, work ethics, and professional responsibilities. A qualitative method was employed, utilizing a literature review approach that analyzed various scientific journals, academic articles, and social phenomena regarding youth professionalism in the digital era. The findings indicate that fundamental professional concepts continue to play a crucial role in shaping the professional character of Generation Z, particularly regarding integrity, adaptability, communication, and collaboration. However, the evolution of digital culture has also introduced challenges, such as declining workplace loyalty, a preference for instant gratification, and inconsistent adherence to professional ethics. This study contributes to the discourse on modern professionalism and offers practical insights for educational institutions and employers seeking to strengthen the professional character development of the younger generation in the Society 5.0 era.